DNA5mC Regulator-Mediated Molecular Clusters and Tumor Microenvironment Signatures in Glioblastoma - Yu, Xinyu; Che, Yijun; Li, Weiyang; Zhang, Peng; Yu, Yunhu; Chen, Jialin; Gong, Ting; Cao, Fang (Frontiers in Cell and Developmental Biology, 2022)
Increasing evidence links DNA methylation to tumor immunity. The impact of DNA methylation (5mC) on the microenvironment surrounding tumors and immunotherapy remains to be clarified. Through clustering gene expression of 20 DNA methylation regulators, this study aimed at systematically analyzing DNA methylation regulator patterns and tumor microenvironment characteristics of TCGA-GBM patients. Various subtypes of glioblastoma exhibit different tumor microenvironments and DNA methylation patterns. Each DNA methylation modification was then assigned a DNA methylation score (DMS). High DMS was associated with a good prognosis. In contrast, the low DMS group had a relatively low survival rate. A correlation was also found between high DMS and enhanced immunotherapy efficacy in two immune checkpoint blocking treatment cohorts. In conclusion, methylation regulation patterns may contribute to glioblastoma progression and differentiation, and may serve as therapeutic targets in the future.